Pengembangan Media Pembelajaran Fisika Pada Topik Gerak Parabola Menggunakan Aplikasi Scratch Untuk Meningkatkan Motivasi Belajar Peserta Didik - Maharani, Devinda Putri; Perdana, Riki (Universitas Negeri Surabaya, 2024)
Students' learning motivation on the topic of parabolic motion is still low because the current learning tends to focus on the teacher so it is less interesting and students are less active. This research aims to develop physics learning media on the topic of parabolic motion using the scratch application to increase students' learning motivation. The method used in this research is Research and Development (R&D) which follows the 4D model (Four-D Models). The instrument used was a feasibility questionnaire which was assessed by 1 expert examining lecturer and 4 prospective physics teacher students. The product feasibility test results from the presentation aspect were 3.10 by the expert examiner lecturer and 3.24 by the students, the content aspect was 2.66 by the expert examiner lecturer and 2.95 by the students, the linguistic aspect was 2.87 by the expert examiner lecturer and 3.02 by students, and the motivation aspect was 3.23 by expert examiners and 3.33 by students. Overall, an average score of 2.96 was obtained by the assessment of expert examiners and 3.13 by prospective physics teacher students. Based on the analysis results obtained, physics learning media on the topic of parabolic motion using the scratch application to increase students' learning motivation is included in the feasible category. Scratch learning media is worthy of being tested or applied to schools. Keywords: parabolic motion, motivation, scratch